2011
DOI: 10.2174/1874613601105010125
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of HIV Infection Among Sexually Active Adults in Kenya: A National Population-Based Survey

Abstract: Objective:To identify factors associated with prevalent HIV in a national HIV survey in Kenya.Methods:The Kenya AIDS Indicator Survey was a nationally representative population-based sero-survey that examined demographic and behavioral factors and serologic testing for HIV, HSV-2 and syphilis in adults aged 15-64 years. We analyzed questionnaire and blood testing data to identify significant correlates of HIV infection among sexually active adults.Results:Of 10,957 eligible women and 8,883 men, we interviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 27 publications
6
26
4
Order By: Relevance
“…Though the strength of association is moderate, the likelihood of HIV positive was 1.43 times more likely among currently married and in union compared to unmarried ones (AOR = 1.43, 95%CI = 1.21, 1.70). Consistent with this study the study conducted in Nairobi Kenya reported that, this risk of HIV/AIDS was higher among widowed compared to unmarried (12)(13)(14). The attribute could be due to, the reason for their divorce and separation could be one of the partner might be affected by HIV infection or He she might have risky behavior.…”
Section: Discussionsupporting
confidence: 79%
“…Though the strength of association is moderate, the likelihood of HIV positive was 1.43 times more likely among currently married and in union compared to unmarried ones (AOR = 1.43, 95%CI = 1.21, 1.70). Consistent with this study the study conducted in Nairobi Kenya reported that, this risk of HIV/AIDS was higher among widowed compared to unmarried (12)(13)(14). The attribute could be due to, the reason for their divorce and separation could be one of the partner might be affected by HIV infection or He she might have risky behavior.…”
Section: Discussionsupporting
confidence: 79%
“…1418 Widowers whose spouses died of HIV disease may have been exposed to high viral load from their partners, which can occur during late-stage disease, 17 but it is also possible that widowed men were sources of infection for their spouses who died from the disease. Studies have also demonstrated that widowers are more likely to engage in high-risk sexual behavior after the death of their spouse and contribute to new HIV infections in the population.…”
Section: Discussionmentioning
confidence: 99%
“…12 It was designed to provide national and provincial data on the sociodemographic, behavioural and biological correlates of HIV infection. 13 All individuals aged 15 to 64 years who were either usually resident in the selected households or visiting the household on the night before the survey were eligible to participate. Interviewers obtained information on the participants' demographic characteristics and sexual behaviour using a structured questionnaire.…”
Section: Methodsmentioning
confidence: 99%